1998
DOI: 10.1016/s0020-7292(95)02403-4
|View full text |Cite
|
Sign up to set email alerts
|

Biology of human trophoblast

Abstract: In order to elucidate the regulation of placental growth, we have characterized the expression of proliferating cell nuclear antigen (PCNA), apoptotic DNA fragmentation and bcl-2 protein in human placenta during pregnancy. PCNA and bcl-2 protein expression were examined by immunohistochemical techniques, while the occurrence of apoptotic DNA fragmentation was assessed by in situ analysis of DNA 3'-end labeling method. Both PCNA expression and apoptotic DNA fragmentation were found in cytotrophoblasts (C-cells)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Decidua and tumor tissues are both characterized by high levels of PCNA expression [13, 14]. Indeed we showed PCNA over expression in cancer for the current study by comparing PCNA expression in matched normal and cancer tissue (Supplementary Table S1, TCGA data).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Decidua and tumor tissues are both characterized by high levels of PCNA expression [13, 14]. Indeed we showed PCNA over expression in cancer for the current study by comparing PCNA expression in matched normal and cancer tissue (Supplementary Table S1, TCGA data).…”
Section: Discussionmentioning
confidence: 54%
“…Yet, PCNA overexpression is imperative for cancer virulence in broad spectrum of functions; thus, PCNA-mediated immune suppression is probably not the leading drive for its cancer-associated overexpression. As with cancer cells, trophoblasts also exhibit high proliferation rates with high levels of PCNA protein [13]. It is possible that the mechanism by which cancer cells suppress NK cell lytic function through NKp44 evolved through the “need” of the trophoblasts to form the placenta and support the fetus for a long duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to roles played by thyrotropin releasing hormone (TRH), thyroid stimulating hormone (TSH) and TRs in thyroid hormone action, proliferating cell nuclear antigen (PCNA) has an important role in testicular proliferation. Studies have revealed that thyroid hormones can positively regulate PCNA expression in diverse tissues, such as the kidney (Witzgall et al 1994), placenta (Mochizuki et al 1998) and brain (Veldhoen et al 2006). However, data on the effects of thyroid hormones in regulating PCNA on the testes are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Gestational Trophoblastic Disease (GTD) refers to a wide spectrum of interrelated conditions ranging from benign hydatidiform mole (HM), invasive mole to malignant choriocarcinoma (26).…”
Section: Discussionmentioning
confidence: 99%